Adult Neurogenesis in Sheep: Characterization and Contribution to Reproduction and Behavior - Lévy, Frederic; Batailler, Martine; Meurisse, Maryse; Migaud, Martine (Frontiers in Neuroscience, 2017)
Sheep has many advantages to study neurogenesis in comparison to the well-known rodent model. Their development and life expectancy are relatively long and they possess a gyrencephalic brain. Sheep are also seasonal breedesr, a characteristic that offers the opportunity to study the role of hypothalamic neurogenesis in the control of seasonal reproduction. Sheep also form social groups in which individuals recognize each other and develop selective and enduring relationship. Adult olfactory neurogenesis could constitute an adaptive response to social behavior by favoring recognition of conspecifics. The present review reveals the distinctive features of the hippocampal, olfactory and hypothalamic neurogenesis in sheep. In particular, the cellular composition and morphological organization of the subventricular zone and the dynamic of neuronal maturation differs from that of rodents. In addition, we show that various physiological conditions, such as seasonal reproduction, gestation and lactation differently modulate these three neurogenic niches. Last, we discuss recent evidence indicating that hypothalamic neurogenesis may play a role in the seasonal control of reproduction and olfactory neurogenesis could be involved in odor processing in the context of maternal behavior.